2012
DOI: 10.4254/wjh.v4.i7.209
|View full text |Cite
|
Sign up to set email alerts
|

Life style modification improves insulin resistance and liver histology in patients with non-alcoholic fatty liver disease

Abstract: Life style modification improves insulin resistance resulting in improvement in ALT and liver histology in NAFLD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
0
6

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 35 publications
3
35
0
6
Order By: Relevance
“…47,48 An Indian study involving 60 NAFLD patients showed regular aerobic exercise for 30 min/day for at least 5 days a week improved insulin resistance resulting in improvement in ALT (decline from 84.8U/L to 41.3 U/L) and liver histology in NAFLD patients. 44 Similar results were obtained from NASH patients (decline in ALT level from 70.5 U/L to 41.5 U/L) also when they were subjected to aerobic exercise of 30 min/day for at least 5 days a week. and pervasive symptoms in people with NASH which contribute to lack of confidence in NASH patients during exercise.…”
Section: Exercisesupporting
confidence: 72%
“…47,48 An Indian study involving 60 NAFLD patients showed regular aerobic exercise for 30 min/day for at least 5 days a week improved insulin resistance resulting in improvement in ALT (decline from 84.8U/L to 41.3 U/L) and liver histology in NAFLD patients. 44 Similar results were obtained from NASH patients (decline in ALT level from 70.5 U/L to 41.5 U/L) also when they were subjected to aerobic exercise of 30 min/day for at least 5 days a week. and pervasive symptoms in people with NASH which contribute to lack of confidence in NASH patients during exercise.…”
Section: Exercisesupporting
confidence: 72%
“…Numerous series of patients showed the association of IR with liver fibrosis on NAFLD (17,(22)(23)(24). In our patient cohort, HOMA-IR was significantly higher in cases with advanced fibrosis (F3-4) versus no fibrosis (6.7 ± 3.8 units fibrosis.…”
Section: Discussionmentioning
confidence: 67%
“…Indeed, muscle complex I activity gradually increased with progressing steatosis and fibrosis in that study. Another study found that lifestyle intervention resulting in greater muscle glucose disposal also improved steatosis and NAFLD (5). Although muscle mitochondrial function was not measured in that study, muscle mitochondrial adaptation could be one mechanism to modulate hepatic fat loading during the development of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This would increase VLDL export and in turn raise circulating triglycerides (TGs) and LDL cholesterol (3). Some exercise studies support this concept in that reversal of muscle insulin resistance decreases HCL and dyslipidemia in humans at risk for type 2 diabetes (4,5).…”
mentioning
confidence: 96%